Pengaruh Praktik Kerja Lapangan, Motivasi Memasuki Dunia Kerja, dan Keaktifan Berorganisasi terhadap Kesiapan Kerja (Business and Accounting Education Journal, 2022)
The purpose of this study was to determine the effect of field work practices, motivation to enter the world of work, and organizational activity on students' work readiness. The population in this study were students of class XII AP SMK Negeri 1 Purwodadi. The total population of the study was 119 from 3 classes with a sample of 92 students calculated based on the Yamene formula with an error rate of 5%. Data collection techniques using a questionnaire. The data analysis technique used multiple regression analysis and descriptive percentage analysis. The results showed: simultaneously field work practice, motivation to enter the world of work, and organizational activity had a positive and significant effect on work readiness by 58.8%, street vendors had a positive and significant effect on work readiness by 4.49%, motivation to enter the world of work had an effect positive and significant effect on work readiness by 10.89%, and organizational activity has a positive and significant effect on work readiness by 9.79%.